Joint DOA and DOD Estimation in Bistatic MIMO Radar without Estimating the Number of Targets - Zaifang Xi; Xiao-feng Wu; Shuyue Wu; Zhijun Tang; Shigang Hu (Journal of Electrical and Computer Engineering)
Existing subspace-based direction finding methods for multiple-input multiple-output (MIMO) radar assume perfect knowledge about the dimension of the signal or noise subspace, which is hard to be established without prior knowledge of the signal environment. In this paper, an efficient method for joint DOA and DOD estimation in bistatic MIMO radar without estimating the number of targets is presented. The proposed method computes an estimate of the noise subspace using the power of R (POR) technique. Then the two-dimensional (2D) direction finding problem is decoupled into two successive one-dimensional (1D) angle estimation problems by employing the rank reduction (RARE) estimator.